Factors Affecting Disclosure of Carbon Emissions in Indonesian Companies - Dwi Indah Lestari (Jurnal Pendidikan Akuntansi & Keuangan, 2023)
This paper aims to identify factors influencing management to disclose the carbon emissions from their operational activities. The carbon disclosure item is measured directly from individual companies’ annual reports and sustainability reports. The sample is selected using a non-probability sampling technique with certain criteria. In this study, 126 samples are collected. This study applies multiple linear analyses and the t-test hypothesis for data analysis. The results showed that environmental performance negatively affects carbon emissions disclosure. At the same time, the type of company and profitability do not affect a company's decision to disclose its carbon emissions. This research differs from other research because it spans a long period from the early adaptation of carbon emissions. Therefore, we can observe how companies in Indonesia gradually disclose their carbon emissions. In general, it can be concluded that companies in Indonesia have started to disclose more items according to Carbon Emission Disclosure Index (CEDI).